Proteomic analysis of outer membrane proteins and vesicles of a clinical isolate and a collection strain of Stenotrophomonas maltophilia - Ferrer Navarro, Mario (2016)
Stenotrophomonas maltophilia is a Gram-negative pathogen with emerging nosocomial incidence that displays a high genomic diversity, complicating the study of its pathogenicity, virulence and resistance factors. The interaction of bacterial pathogens with host cells is largely mediated by outer membrane proteins (OMPs). Indeed, several OMPs of Gram-negative bacteria have been recognized as important virulence factors and targets for host immune recognition or to be involved in mechanisms of resistance to antimicrobials. OMPs are also present in outer membrane vesicles (OMVs), which bacteria constitutively secrete to the extracellular milieu and are essential for bacterial survival and pathogenesis. Here, we report the characterization of the OMP and native OMV subproteomes of a clinical isolate (M30) and a collection strain (ATCC13637) of S. maltophilia. We had previously shown that the ATCC13637 strain has an attenuated phenotype in a zebrafish model of infection, as well as a distinct susceptibility profile against a panel of antimicrobials. The protein profiles of the OMP and OMV subproteomes of these two strains and their differences consequently point at pathogenesis, virulence or resistance proteins, such as two variants of the quorum-sensing factor Ax21 that are found to be highly abundant in the OMP fraction and exported to OMVs.BIOLOGICAL SIGNIFICANCE:Stenotrophomonas maltophilia is rapidly climbing positions in the ranking of multidrug-resistant pathogens that are frequently isolated in hospital environments. Being an emerging human pathogen, the knowledge on the factors determining the pathogenicity, virulence and resistance traits of this microorganism is still scarce. Outer membrane proteins (OMPs) and vesicles (OMVs) are key elements for the interaction of Gram-negative bacteria with their environment -including the host-and have fundamental roles in both infection and resistance processes. The present study sets a first basis for a phenotype-dependent characterisation of the OMP subproteome of S. maltophilia and complements very recent work on the OMV subproteome of this species. The variability found among even two strains demonstrates once more that the analysis of genotypically and phenotypically distinct isolates under various conditions will be required before we can draw a significant picture of the OMP and OMV subproteomes of S. maltophilia.